Innovating for Trust 2017
DOI: 10.4337/9781785369483.00006
|View full text |Cite
|
Sign up to set email alerts
|

Innovating for trust

Abstract: Innovation, in short, is the implementation of new ideas, products or processes (Hurley and Hult, 1998), or taking on a process perspective, 'the generation, acceptance, and implementation of new ideas, processes, products or services' (Thompson, 1965, p. 4). Successfully launching

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…• Perceived over-complexity and over-turbulence, i.e., adverse cognitive conditions, often render real-world socio-economic CAS counterproductive, generating individual and systemic rigidities through low general trust, entailing myopia, winner-takes-all cultures, reduced innovation or some flawed or pseudo innovation, often with considerable social costs and decreasing employment, while proper levels of complexity and change/stability would provide conditions of realistic self-confidence and future investments and innovation of agents (e.g., Bloom et al, 2005;Elsner & Schwardt, 2014;Kleinknecht et al, 2016;Grant & Moses, 2017;Lueders et al, 2017;Sautua, 2017;Bertani et al, 2019;Coad et al, 2021). • Financialization, then, through its often-asymmetric information structure 8 and thus dominant incentives to short-run redistribution, defection and exploitation, profit reaping, and rent-seeking (rather than value creation), reinforces myopia and a winner-takes-all culture, reduces social commitment, and may displace comprehensive and productive behavioural and technological innovation (e.g., García-Vega & Huergo, 2017; Kingston, 2017; Lueders et al, Bettignies & Ries, 2023).…”
Section: Innovation and Information As A Prime Field Of Complexity Ec...mentioning
confidence: 99%
See 1 more Smart Citation
“…• Perceived over-complexity and over-turbulence, i.e., adverse cognitive conditions, often render real-world socio-economic CAS counterproductive, generating individual and systemic rigidities through low general trust, entailing myopia, winner-takes-all cultures, reduced innovation or some flawed or pseudo innovation, often with considerable social costs and decreasing employment, while proper levels of complexity and change/stability would provide conditions of realistic self-confidence and future investments and innovation of agents (e.g., Bloom et al, 2005;Elsner & Schwardt, 2014;Kleinknecht et al, 2016;Grant & Moses, 2017;Lueders et al, 2017;Sautua, 2017;Bertani et al, 2019;Coad et al, 2021). • Financialization, then, through its often-asymmetric information structure 8 and thus dominant incentives to short-run redistribution, defection and exploitation, profit reaping, and rent-seeking (rather than value creation), reinforces myopia and a winner-takes-all culture, reduces social commitment, and may displace comprehensive and productive behavioural and technological innovation (e.g., García-Vega & Huergo, 2017; Kingston, 2017; Lueders et al, Bettignies & Ries, 2023).…”
Section: Innovation and Information As A Prime Field Of Complexity Ec...mentioning
confidence: 99%
“…With increasing futurity, an increasing average expectation "to meet (again)", as, e.g., in a decreasing population or "arena" size (a smaller interaction arena, neighbourhood, peer group, locality, firm cluster, firm network etc. ), or with less enforced disembedding/uprooting mobility, thus with less perceived turbulence, or, put differently, with a stronger expectation of meeting future cooperative behaviour, a higher general trust, the disposition towards cooperation will increase (e.g., Elsner, 2012;García-Vega & Huergo, 2017;Lueders et al, 2017;van der Wouden, 2020).…”
Section: The Example Of the "Evolution Of Cooperation": Behavioural I...mentioning
confidence: 99%
“…Trust is shown to play a crucial role in understanding the acceptance of innovative technology [21]. In fact, [12] reported that trust determines the use or rejection of automation and willingness to rely on automation in certain situations.…”
Section: A Trust Understanding and Modelingmentioning
confidence: 99%
“…Service design refers not only to the ability of a company to come up with an offer on the market, but at the same time, to the design of that offer. (Lüders, Andreassen, Clatworthy and Hillestad, 2017) It puts the consumer at the forefront, but does not simply reduce to the identification of the consumers' needs, wishes; in many situations, the "designer" tries to discover what the consumer will want in the future, even if he/she can not express his/her wish at this time. Service design is based on the way the different actors create value together with consumers, trying to understand the needs and expectations of the latter.…”
Section: Value-oriented Brand-design Relationshipmentioning
confidence: 99%